DESIGN AND DEVELOPMENT CONTROLLING INGREDIENTS INFORMATION SYSTEM FOR KITCHEN DEPARTMENT AT AMARIS HOTEL EMBONG MALANG SURABAYA - christophorus bimo; henry bambang setyawan; valentinus roby hananto (Jurnal Sistem Informasi Universitas Dinamika, 2019)
Amaris Hotel Embong Malang Surabaya is a 3 stars hotel that carries the concept of “bed & breakfast”. There is a problem on controlling the cooking ingredients at the Kitchen Department. The problem is, this Department don’t have a proper ingredients usage documentation. As a result the Kitchen Department’s Staff cannot ensure the quantity of ordering the cooking ingredients, and because of this, lacks and excess of ingredients is often occurs. To overcome this problem, an information system for controlling the cooking ingredients in the Kitchen Department of Amaris Hotel Embong Malang Surabaya was built. The system applied an Economical Order Quantity methods to calculate the most economic order quantity for each ingredients. Reorder point methods to determine the reorder point of each ingredients where Safety Stocks is based on calculation of the ingredients usage. The test and evaluation result shows that system can minimize the ordering and holding cost of cooking ingredients and able to control the stock so there are no more excess and lacks of ingredients. The reports of purchases, receipts, and usage of ingredients already fulfilled the information needs of the Head of Kitchen Department.Keywords: Economical Order Quantity, Safety Stock, Reorder Point.